Influences of protein levels on the cerebrospinal fluid distribution of ceftazidime & ceftriaxone in the cerebrospinal fluid of patients with inflamed meningitis. Issue 8 (August 2022) - Ichinose, Naoki; Yoshikawa, Gakushi; Fukao, Eri; Takahata, Tomoaki; Ichisawa, Mai; Enoki, Yuki; Taguchi, Kazuaki; Oda, Toshimi; Tsutsumi, Kazuo; Matsumoto, Kazuaki
Abstract: Introduction: Ceftazidime and ceftriaxone are used to treat various gram-negative pathogens, such as Streptococcus pneumoniae and Pseudomonas aeruginosa, and have shown excellent therapeutic efficacy against bacterial meningitis. However, there is insufficient information on the pharmacokinetic characteristics of their cerebrospinal distribution. Here, we investigated the association of clinical laboratory data in cerebrospinal fluid with ceftazidime and ceftriaxone concentration in the cerebrospinal fluid of patients with inflamed meningitis. Methods: Cerebrospinal fluid samples were collected from eight adult patients with inflamed meningitis who intravenously received either ceftazidime or ceftriaxone (ceftazidime: a total of 25 samples from three patients, ceftriaxone: a total of 12 samples from five patients). Total cell number, protein concentration, and glucose concentration in the cerebrospinal fluid were retrospectively collected from electronic medical charts. All ceftazidime and ceftriaxone concentrations in the cerebrospinal fluid were determined using high-performance liquid chromatography. Results: Both ceftazidime and ceftriaxone concentrations in cerebrospinal fluid correlated with protein concentration in cerebrospinal fluid; however, no significant correlation was observed in total cell number and glucose concentration in cerebrospinal fluid. Conclusions: This is the first report on the relationship between the cerebrospinal distribution of these antibiotics and clinical laboratory data in cerebrospinal fluid of adult patients with meningitis.